Efecto de las fitohormonas ácido indolbutírico (AIB) y ácido naftalenacético (ANA) para la propagación de esquejes de patita de paloma (Iresine herbstii). - Tovar Tovar, Jonathan Joel (2022)
This research was conducted with the objective of testing various doses, 500, 1000 and 1500 ppm of phytohormones indolbutyric acid (IBA) and naphthaleneacetic acid (NAA) in Iresine herbstii which is a species of the Amaranthaceae family, in the sector of 4 sleeves was used a completely randomized design, with 8 treatments and 4 replicates, subjecting all variables under study to an analysis of variance to determine the statistical significance and Duncan's test.